Inovasi Sabun Aromaterapi dari Daun Cengkeh Sebagai Media Booklet berbasis Android pada Pembelajaran Kimia Terapan - Mala Nirmala; Kartini Rahman Nisa; Fauzia Hulopi (Jurnal Penelitian Pendidikan IPA, 2022)
The essential oil content of cloves can be used as a base for aromatherapy soap. The manufacturing process is an example of implementing applied chemistry in everyday life that utilizes local Maluku wisdom. The purpose of this study was to create an aromatherapy soap innovation from clove leaves as a valid android-based booklet media in applied chemistry learning. This research was conducted by making aromatherapy soap from clove leaves and testing the quality of the soap and then making an android-based booklet with materials for making aromatherapy soap to support applied chemistry learning. The android-based booklet media that was created was validated by experts and then analyzed using the content validity coefficient formula according to Gregory. The results showed that aromatherapy soap from clove leaves met the quality standards of hand-washing liquid soap. And the best treatment of aromatherapy soap is at a concentration of 15% with a pH of 6.98, free alkali of 0.02%, and total plate count of 6.00 x 100. The results of the content validity analysis obtained information that the android-based booklet media in applied chemistry learning has met the criteria valid where the overall content validity coefficient is 75%. The resulting android-based booklet media can make it easier for students to learn applied chemistry online and offline